2022
DOI: 10.1002/cssc.202200365
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐First Depolymerization of Lignocellulose into Monophenols over Carbon Nanotube‐Supported Ruthenium: Impact of Lignin Sources

Abstract: Lignin‐first depolymerization of lignocellulosic biomass into aromatics is of great significance to sustainable biorefinery. However, it remains a challenge, owing to the variance between lignin sources and structures. In this study, ruthenium supported on carbon nanotubes (Ru/CNT) exhibits efficient catalytic activity toward lignin hydrogenolysis to exclusively afford monophenols in high yields. Catalytic tests indicate that the yields of aromatic monomers are related to lignin sources and decrease in the ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 96 publications
0
33
0
Order By: Relevance
“…The DFT calculation analysis confirmed that the high selectivity of the catalyst for the target product arenes was due to strong adsorption, selective activation of C–O bonds in phenolic compounds, and the strong metal–support interaction between Ru and NbOx species. Along this achievement, several groups have also recently demonstrated effective methods and strategies for the conversion of lignin to BTX, leading to exciting initial developments in this field. ,, Although some inspiring achievements have been furnished, some challenges that need further in-depth study still exist. It is noteworthy that the reaction pathway for the lignin depolymerization reaction and the subsequent phenolic HDO reaction depends on the structure of the feedstock, which largely determines the product selectivity.…”
Section: Potential Catalysts and Conditions Of The Conversion Of Phen...mentioning
confidence: 99%
“…The DFT calculation analysis confirmed that the high selectivity of the catalyst for the target product arenes was due to strong adsorption, selective activation of C–O bonds in phenolic compounds, and the strong metal–support interaction between Ru and NbOx species. Along this achievement, several groups have also recently demonstrated effective methods and strategies for the conversion of lignin to BTX, leading to exciting initial developments in this field. ,, Although some inspiring achievements have been furnished, some challenges that need further in-depth study still exist. It is noteworthy that the reaction pathway for the lignin depolymerization reaction and the subsequent phenolic HDO reaction depends on the structure of the feedstock, which largely determines the product selectivity.…”
Section: Potential Catalysts and Conditions Of The Conversion Of Phen...mentioning
confidence: 99%
“…Apart from its calorific value, lignin is the second most copious renewable resource after cellulose. It retains great value-added potential for the synthesis of lucrative compounds due to its distinctive aromatic skeleton. Converting lignin from agroforestry and paper industry wastes into high-value-added monomeric phenols not only helps the environment but also meets the development of biorefineries . For this reason, the ″lignin-first″ biorefining strategy, which incorporates lignin valorization into the design phase, has shown maximum utilization of lignocellulose. In this case, the natural lignin is removed from wood flour and converted to soluble aromatic compounds, while retaining (hemi)­cellulose as the insoluble part. A series of metal catalysts have been developed in the reductive catalytic fractionation (RCF) of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…A series of metal catalysts have been developed in the reductive catalytic fractionation (RCF) of biomass. For example, the noble-metal catalysts of Pd and Ru , are used in the RCF of lignocellulose to produce monophenol compounds with a content in the range of 20–55 wt %. However, the frequent use of expensive precious metals is the main problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,16 Choice of substrate also has major implications for both monomer identity and overall yields, with hardwoods being more amenable to depolymerization and high monomer yields compared to softwoods and grasses. 17,18 Investigations of the impact of catalyst identity have mainly focused on the selectivity to different product monomers, with comparably less emphasis on the rate of stabilization. Typically, Ru/C, Ni/C, and Rh/C are reported to form propyl substituted monomers through a combination of hydrodeoxygenation and hydrogenation, 7,10,15,19 whereas Pd/C forms propanol substituted monomers.…”
Section: Introductionmentioning
confidence: 99%
“…9,12,16 Choice of substrate also has major implications for both monomer identity and overall yields, with hardwoods being more amenable to depolymerization and high monomer yields compared to softwoods and grasses. 17,18…”
Section: Introductionmentioning
confidence: 99%